Pesatnya Perkembangan Sains dan Teknologi: Relevansi dan Tantangan Pendidikan Islam Indonesia Perspektif Integrasi Interkoneksi - Sa’adah, Qorinatus (Universitas Islam Tribakti Lirboyo Kediri, 2024)
This study aims to investigate the relevance and challenges confronting Islamic education amidst the rapid advancements in technology. Employing a Descriptive-Qualitative methodology with a library research approach, this research draws primarily from books, journals, documents, magazines, and other pertinent sources. The findings of this study underscore the significant challenges facing Islamic education, primarily stemming from the dichotomous paradigm inherent within it. This paradigm often delineates between religious-based knowledge and general science (social science), thus impeding the adaptability of Islamic education to the evolving landscape of the modern era. Furthermore, the pervasive influence of technology and science profoundly impacts the realm of education, necessitating continual relevance and adaptability to equip students with the requisite skills and knowledge to navigate the swiftly changing times.In conclusion, the study highlights the imperative for Islamic education to overcome inherent dichotomies and embrace interdisciplinary approaches to remain relevant and responsive to contemporary challenges. By integrating Islamic teachings with modern knowledge and technology, Islamic education can effectively prepare students for the complexities of the contemporary world while upholding the core values of Islam.